New reactive silicone resins - Rościszewski, P.; Sołtysiak, J.; Łubkowska, M.; Walkowiak, Z. (Polimery, 2021)
The synthesis of a new class of reactive silicone resins containing vinyl and methacryloxypropyl substituents has been described. These resins are very fast curing (in several tens of seconds) in the temperature range of 100 to 150 °C by polymerization reaction using peroxide initiators. Both the solutions of liquid resins and their mixtures with various polymerizable monomers as well as organic and organosilicon polymers can be used as coating materials, binders and in the modification of polymers.